The potential of village cereal stockists in facilitating rural women's access to improved seed of non-hybrid legume seed in Eastern Kenya - Njuguna-Mungai, Esther (International Crops Research Institute for the Semi-Arid Tropics, 2018)
Presented by Esther Njuguna-Mungai (ICRISAT), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.